2007
DOI: 10.1186/gb-2007-8-8-r166
|View full text |Cite
|
Sign up to set email alerts
|

The roles of binding site arrangement and combinatorial targeting in microRNA repression of gene expression

Abstract: Factors affecting repression by microRNAs

A genome wide analysis of factors affecting repression of mRNAs by microRNAs reveals roles for 3'UTR length, the number of target sites on the mRNA and the distance between pairs of binding sites.

Abstract Background: MicroRNAs (miRNAs) are small noncoding RNAs that bind mRNA target transcripts and repress gene expression. They have been implicated in multiple diseases, such as cancer, but the mechanisms of this involvement are not well understood. Given the com…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 63 publications
(94 reference statements)
4
131
0
1
Order By: Relevance
“…Consistent with this model, the down-regulation of miRNA expression in airway epithelial cells with smoking may be a consequence of repetitive airway injury that results in accumulation of proliferating and dedifferentiated cells. Several studies have sought to establish regulatory relationships between miRNA and mRNA expression (33)(34)(35)(36). By collecting miRNA and mRNA from the same samples, we were able to discover correlations between miRNA and mRNA expression profiles both across patient groups and within individuals.…”
Section: Differentially Expressed In Vivomentioning
confidence: 82%
“…Consistent with this model, the down-regulation of miRNA expression in airway epithelial cells with smoking may be a consequence of repetitive airway injury that results in accumulation of proliferating and dedifferentiated cells. Several studies have sought to establish regulatory relationships between miRNA and mRNA expression (33)(34)(35)(36). By collecting miRNA and mRNA from the same samples, we were able to discover correlations between miRNA and mRNA expression profiles both across patient groups and within individuals.…”
Section: Differentially Expressed In Vivomentioning
confidence: 82%
“…The two most important are discussed in the next two sections are (I) the binding site accessibility and (II) stoichiometry between a small RNA ant its target (or binding kinetics). Other factors, which might contribute to silencing in a context-dependent manner are, for example, alternative polyadenylation and arrangement of miRNA binding sites in 3'UTRs might cause different effects in different cells (Hon and Zhang, 2007;Majoros and Ohler, 2007;Nam et al, 2014a). In particular, there was a strong preference reported for targets to be located in close vicinity of the stop codon and the polyadenylation sites.…”
Section: Other Key Factors Influencing Target Recognition and Repressionmentioning
confidence: 99%
“…It has been demonstrated that under certain cellular conditions a stable secondary structure could be unfolded to provide access to a miRNA target site. This miRNA mediated regulation can be exploited by a cell during stress response or in tissue specificity (29). There is evidence that two miRNAs may bind to a target mRNA in coordination.…”
Section: Mir-polymorphism In Mirna Target Sitesmentioning
confidence: 99%